Preparation of new o-carboxyanilinotellurium(IV) bromides and their dyeing properties - Topal, G; Temel, H; Yavuz, Ö; Coskun, M; Sekerci, M (Marcel Dekker Inc, 2001)
This study represents a new synthesis of two organotellurium compounds and their dyeing properties. The structure of these tellurium derivatives are proposed based on elemental analyses, IR, UV-Vis, H-1 and C-13 NMR spectra and thermogravimetric analyses (TGA).
Keywords: Uo2(Vi) Complexes; Co(Ii); Cu(Ii); Ni(Ii); Extraction; Ligands; Cl